Pengelolaan Limbah Plastik di Pantai Paseban: Tinjauan Implementasi dalam Pembelajaran Siswa TK Dewi Masyitoh - Supeno, Supeno; Fershanda Vivi Hartono; Ni’matun Nailil Izza; Delfi Vidia Almira; Farhan Faillasuf Abdillah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The issue of plastic pollution in the Paseban Beach area has become a serious concern as plastic waste accumulation threatens marine ecosystems and environmental health. This initiative aims to design a plastic waste management system in Paseban Village, integrated as an educational tool for Dewi Masyitoh Kindergarten students. The activities involved field observations, interviews, and experiments in waste management-based learning. The results show that the plastic waste management program, involving recycling activities such as creating collages and ecobricks, successfully enhances students' knowledge and skills in waste management. The findings conclude that integrating waste management into educational activities not only strengthens environmental education for students but also provides sustainable solutions for the community in addressing plastic waste issues. These results highlight the importance of implementing similar programs in other areas to raise environmental awareness from an early age.